Searching for a Work-Life Balance in Your Health and Social Services Career? - Townshippers' Association; Dialogue McGill (2024)

Health and Social Services Career Opportunities Training Guide : Eastern Townships Region - Townshippers' Association; Dialogue McGill (2023)

Committee Examines Rules for Posting Bilingual Positions - Quebec Community Groups Network (QCGN) (2022)

La commission examine les règles relatives à l’affichage des postes bilingues - Quebec Community Groups Network (QCGN) (2022)

Harnessing your Transferable Skills in a COVID-19 Economy - Khamala, Maya (2021)

Job Search Mentorship During COVID-19 - Khamala, Maya (2021)

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Programme de maintien en poste : Monitoring des stagiaires - Storr, Caroline; Hendrickson, Mary (2018)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

Earn While you Learn Sutton : A CEDEC Collaboration Story - Community Economic Development and Employability Corporation (CEDEC)
Tourism is a major economic driver in the Sutton area, however, labour shortages are hampering growth. Through innovative skills training, tourism sector employers are attracting new talent and through upskilling they are retaining and promoting their existing workforce to take on new responsibilities and secure year-round employment.

Job Hunting Tips for Introverts - Khamala, Maya

The "Candidate Experience" Evaluation the Hiring Process - Khamala, Maya

“Tell Me About Yourself" : How to Answer the Hardest Interview Question - Morgenstern-Clarren, Rachel

Jump Start Your Job Search : Readiness Questionnaire - Youth Employment Services (YES)